Pengaruh Profitabilitas, Leverage, Likuiditas, Dan Ukuran Perusahaan Terhadap Stock Returns - Winny, Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to examine the effect of profitability, leverage, liquidity and firm size on return of stock in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018 period. Sampling techniques using purposive sampling method. Data is processed using Eviews 9.0. This study uses 61 companies within 3 years period and the result using 183 unit sampling. The results of this study indicate that profitability, leverage, and liquidity have no effect on return of stock, differing with firm size that significantly influence the return of stock.